Guilt induced message elaboration and effect on attitude towards value adoption: an ANCOVA approach - Chatterjee, Rajat Subhra; Haron, Sharifah Azizah; Osman, Syuhaily; Muhammad Arif, Afida Mastura (Human Resource Management Academic Research Society, 2022)
Engagement in Voluntary Simplicity behaviour can be strongly attributed to contributing towards environmental protection through consumption reduction. The attitudinal inclination towards adopting VS values has mostly been observed on the degree of awareness and current behaviour of individuals. However similar to sustainability practices, VS adoption can also be instigated through external influences. In the present study, a pioneer effort is being undertaken to observe the degree of persuasive intent that can be created through the intervention of anticipatory guilt, argument quality, and source credibility manipulation. The sample was drawn from the Malaysian youth population using the multi-stage cluster sampling method. The result of ANCOVA analysis shows significant direct effects on each of the VS values namely material simplicity, social responsibility, self-sufficiency, and spiritual growth. We also found strong interaction effects of anticipatory guilt and argument quality at high and low intervention levels towards youth attitude.